PENGARUH PENGETAHUAN KOMPUTER DAN SIKAP INOVATIF GURU TERHADAP EFEKTIFITAS KERJA GURU SMPN KECAMATAN LANGGAM KABUPATEN PELALAWAN - Suhailis Suhailis; Isjoni Isjoni; Elfis Suanto (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2022)
This study aims to (1) determine the effect of computer knowledge on the effectiveness of teachers' work, (2) innovative attitudes affect the effectiveness of teachers' work, (3) computer knowledge and innovative attitudes jointly affect the effectiveness of teachers' work. Research respondents were teachers of SMPN Langgam Subdistrict, Pelalawan Regency, totaling 100 people with a sample of 89. The data was collected through the distribution of questionnaires. The data analysis used is descriptive analysis and inferential statistical analysis. The instrument reliability coefficient was calculated using the Cronbach alpha formula. The results showed that there was a positive and significant effect of computer knowledge on teacher work effectiveness of 0.558, and there was a positive and significant influence of innovative attitudes on teacher work effectiveness of 0.525. Meanwhile, together there is the effect of computer knowledge and work motivation on the effectiveness of the teacher's work of 0.677.